Gel particles, high-strength porous concrete and preparation method and application thereof
Patent Information
- Application Number
- CN202611452732.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-18
- Publication Date
- 2026-10-23
AI Technical Summary
然而水泥基材料内部为高碱度和高离子浓度的环境,其中Ca²+等多价离子会影响这些种类水凝胶的吸液、保液和释液性能,使其实际吸液倍率下降,释水过程难以稳定调控,影响其稳定成孔和持续内养护效果
发明提供了一种凝胶颗粒,使用奇亚籽皮多糖和聚乙烯醇制备具有稳定的三维网络结构的聚合物凝胶,奇亚籽皮多糖所含的丰富羟基(-OH)能够提高纳米二氧化硅的结合能力,而纳米二氧化硅所提供的反应位点能够与水泥基材料内部环境中的Ca2+反应,延缓Ca2+进入颗粒内部的时机;待Ca2+逐步进入凝胶颗粒后,破坏奇亚籽皮多糖形成的三维网络结构,使凝胶颗粒收缩并释放内部储存的水和硅源,在空腔壁区域继续进行水化反应,生成C-S-H类水化产物,增强空腔壁区域的力学性能,兼顾内养护、孔壁增强和力学性能保持的作用。
Smart Images

Figure CN122958095A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of building materials technology, specifically relating to a gel particle, high-strength porous concrete, its preparation method and application. Background Technology
[0002] The information disclosed in this background section is intended only to enhance understanding of the overall background of the invention and is not necessarily to be construed as an admission or in any way implying that such information constitutes prior art known to those skilled in the art.
[0003] Introducing lightweight aggregates, foaming systems, aeration reactors, or pore-forming materials into high-strength concrete creates a porous structure within the cement matrix, resulting in high-strength porous concrete. This reduces the apparent density and thermal conductivity of the material while maintaining a certain compressive strength, and endows it with functions such as thermal insulation, sound absorption and noise reduction, and lightweight components. The porous structure within the cement matrix can be achieved using hydrogels. The water-absorbing and expanding hydrogels support the cavity space during the cement curing stage and shrink to form cavities later upon water release.
[0004] Existing hydrogel-based internal curing materials mostly use synthetic polymers such as polyacrylates and polyacrylamide as their main raw materials. However, the interior of cement-based materials is a high-alkalinity and high-ion-concentration environment, where Ca²⁺… + Isovalent ions can affect the liquid absorption, retention, and release properties of these types of hydrogels, reducing their actual liquid absorption ratio and making it difficult to stably control the water release process, thus affecting their stable pore formation and continuous internal curing effect. Ultimately, this has an adverse impact on the mechanical properties of high-strength porous concrete. Summary of the Invention
[0005] To address the shortcomings of existing technologies, the present invention aims to provide gel particles, high-strength porous concrete, their preparation methods, and applications. The main components of the gel particles are chia seed peel polysaccharide and polyvinyl alcohol, which can stably release water within the internal environment of cement-based materials. The sodium silicate contained in the gel particles can provide internal curing, enhance the mechanical properties of the cavity wall area, and thus ensure the performance of high-strength porous concrete.
[0006] To achieve the above objectives, the technical solution of the present invention is as follows: In a first aspect, a gel particle includes a hydrogel core material and a nano-silica layer covering the hydrogel core material. The raw materials for preparing the hydrogel core material include chia seed peel polysaccharide and polyvinyl alcohol in a mass ratio of (6~8):(2~4). The hydrogel core material contains an aqueous solution of sodium silicate.
[0007] Secondly, the method for preparing the aforementioned gel particles includes the following steps: Chia seed peel polysaccharide and polyvinyl alcohol were mixed in a set mass ratio to form a mixture, and then the mixture was freeze-thawed to obtain a hydrogel. After the first drying, crushing and sieving, polymer particles were obtained. The surface of polymer particles is wetted with a nano-silica dispersion, followed by a second drying process to obtain second polymer particles with an externally coated nano-silica layer. The second polymer particles were placed in an aqueous sodium silicate solution and absorbed to obtain the gel particles.
[0008] Thirdly, a high-strength porous concrete comprises the following components in parts by weight: 570-670 parts cement, 90-150 parts fly ash, 90-120 parts silica fume, 550-650 parts quartz sand, 620-680 parts diabase fine aggregate, 155-195 parts water, 12-18 parts polycarboxylate superplasticizer, and 3.0-4.5 parts of the above-mentioned gel particles.
[0009] Fourthly, the above-mentioned method for preparing high-strength porous concrete includes the following steps: Cement, fly ash, and silica fume are mixed to obtain the first mixture; The first mixture, quartz sand, diabase fine aggregate, and 65-75% water by volume are mixed to obtain the second mixture; The second mixture, the gel particles, the remaining water, and the polycarboxylate superplasticizer are mixed to obtain a high-strength porous concrete mixture. The high-strength porous concrete mixture is poured, cured, demolded, and post-cured to obtain the high-strength porous concrete.
[0010] Fifthly, the application of the aforementioned high-strength porous concrete in building energy-saving materials, building acoustic materials, and traffic noise reduction materials.
[0011] The beneficial effects of this invention are as follows: The invention provides a gel particle, which uses chia seed peel polysaccharide and polyvinyl alcohol to prepare a polymer gel with a stable three-dimensional network structure. The abundant hydroxyl groups (-OH) contained in chia seed peel polysaccharide can improve the binding ability of nano-silica, while the reaction sites provided by nano-silica can react with Ca in the internal environment of cement-based materials. 2+ The reaction, delaying Ca 2+ The timing of Ca entering the interior of the particle; 2+ After gradually entering the gel particles, the three-dimensional network structure formed by chia seed peel polysaccharides is disrupted, causing the gel particles to shrink and release the water and silicon sources stored inside. The hydration reaction continues in the cavity wall region, generating CSH-type hydration products, which enhance the mechanical properties of the cavity wall region, thus taking into account the functions of internal maintenance, pore wall reinforcement, and mechanical property preservation. Attached Figure Description
[0012] The accompanying drawings, which form part of this invention, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an improper limitation of the invention.
[0013] Figure 1 This is a schematic diagram of the preparation method of gel particles in Example 1.
[0014] Figure 2 This is a characterization result diagram of the pore structure in Example 2.
[0015] Figure 3 This is a schematic diagram of the reaction process inside the high-strength porous concrete in Example 2, where (A) is the initial stage, (B) is the outer layer reaction stage, (C) is the water and silicon release stage, and (D) is the pore wall reinforcement stage.
[0016] Figure 4 The figures provided are statistical charts of the compressive strength and autogenous shrinkage rate of high-strength porous concrete in various embodiments and comparative examples.
[0017] Figure 5 The figures provided are statistical charts of the average sound absorption coefficient and thermal conductivity of high-strength porous concrete in various embodiments and comparative examples. Detailed Implementation
[0018] It should be noted that the following detailed descriptions are exemplary and intended to provide further illustration of the invention. Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains.
[0019] It should be noted that the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the scope of exemplary embodiments according to the invention. As used herein, the singular form is intended to include the plural form as well, unless the context clearly indicates otherwise. Furthermore, it should be understood that when the terms "comprising" and / or "including" are used in this specification, they indicate the presence of features, steps, operations, devices, components, and / or combinations thereof.
[0020] The chia seed peel polysaccharide and corn root mucilage polysaccharide used in the following specific embodiments are both commercially available products.
[0021] One or more embodiments of the present invention provide a gel particle comprising a hydrogel core and a nano-silica layer covering the hydrogel core. The raw materials for preparing the hydrogel core include chia seed peel polysaccharide and polyvinyl alcohol in a dry mass ratio of (6~8):(2~4). The hydrogel core contains an aqueous solution of sodium silicate.
[0022] Chia seed peel polysaccharide contains numerous hydrophilic groups such as hydroxyl and carboxyl groups in its molecular chains. When dried chia seed peel polysaccharide re-exposes water or a low-concentration sodium silicate aqueous solution, the liquid can penetrate the inter-chain regions of the polysaccharide and promote chain re-extension, forming a network structure with viscoelasticity and water-binding ability. This results in good wetting and rehydration capabilities, and the dense water-binding network increases liquid storage capacity and reduces sodium silicate diffusion and leakage before application. Furthermore, hydrogen bonds can form between chia seed peel polysaccharide and polyvinyl alcohol (PVA) molecular chains, maintaining the continuity of the gel network. This reduces the migration and leakage of pre-absorbed liquid before use. Chia seed peel polysaccharide also exhibits good film-forming and gel-forming compatibility with PVA. Other types of polysaccharides (such as corn root mucilage polysaccharide and wheat root mucilage polysaccharide) have weaker binding ability to sodium silicate, leading to a higher risk of early leakage; their film-forming / gel-forming compatibility with PVA is also lower, resulting in insufficient internal network density and poor rehydration ability after drying.
[0023] Optionally, the concentration of the sodium silicate aqueous solution is 2-5 wt%, and the sodium silicate aqueous solution accounts for 60-90 wt% of the mass of the hydrogel core material.
[0024] Optionally, the particle size of the gel particles is 0.4 to 3.2 mm, and the thickness of the nano-silica layer is 0.1 to 1.0 μm.
[0025] One or more embodiments of the present invention provide a method for preparing the above-mentioned gel particles, comprising the steps of: Chia seed peel polysaccharide and polyvinyl alcohol were mixed in a set mass ratio to form a mixture, and then the mixture was freeze-thawed to obtain a hydrogel. After drying, crushing and sieving, polymer particles were obtained. The surface of polymer particles is wetted with a nano-silica dispersion and then dried to obtain a second polymer particle with an externally coated nano-silica layer. The second polymer particles were placed in an aqueous sodium silicate solution and absorbed to obtain the gel particles.
[0026] In the above process, a hydrogel is first prepared using a mixture of chia seed peel polysaccharide and polyvinyl alcohol, and then dried to obtain polymer particles. The polymer particles are dry network particles with capillary channel structure, which is conducive to the wetting of the particle surface by the nano silica dispersion and its entry into the shallow pores. After being treated with the nano silica dispersion and dried again, the nano silica can be deposited and adsorbed on the particle surface. If the high water content swelling gel is directly treated, the dispersion is easily diluted by the surface aqueous phase and diffuses into the particle interior, which is not conducive to the formation of surface enrichment structure. The silanol groups on the surface of nano-silica form hydrogen bonds and interfacial adsorption with the hydroxyl and carboxyl groups on the polysaccharide and PVA chains. During the particle drying process, nano-silica can also be deposited and embedded in the shallow pores on the surface of the dried gel particles, thus fixing nano-silica on the surface of polymer particles. Then, the second polymer particles are placed in an aqueous sodium silicate solution to absorb the liquid, so that the external silicon source is mainly distributed on the particle surface and the internal silicon source is mainly stored in the gel network. If the sodium silicate solution is pre-absorbed before loading nano-silica, the particles are in an expanded state, and subsequent drying may cause problems such as sodium silicate migration, precipitation, and cracking or detachment of the surface loading structure.
[0027] Optionally, the chia seed peel polysaccharide is a polysaccharide mucilage material obtained by water extraction, separation, and drying of chia seeds, with a molecular weight of approximately 0.8 × 10⁻⁶. 6 ~2.0×10 6 Da, the hydrolysis products include xylose, glucose and 4-O-methylglucuronic acid, etc.; the solid content in the mixture is 7~10wt%, and the solid content refers to the total content of chia seed peel polysaccharide and polyvinyl alcohol.
[0028] Optionally, the freeze-thaw cycle method includes: freezing the mixture at -20 to -10 ℃ for 8 to 12 h, then thawing it at 20 to 30 ℃ for 4 to 8 h, repeating the freeze-thaw treatment 2 to 3 times; this causes the polyvinyl alcohol molecular chains to align closely together to form dense microcrystalline regions, which, together with the uncrystallized segments, hydrogen bonds, and molecular chain entanglements, constitute a three-dimensional network structure. Increasing the number of freeze-thaw cycles can improve the network density, crystallinity, and mechanical stability of the PVA gel, and reduce its equilibrium swelling degree; if the number of freeze-thaw cycles is too few, there will be insufficient crystalline cross-linking points, resulting in low gel network stability and wet strength, and the particles are prone to deformation, breakage, or premature release during rehydration and concrete mixing; if the number of freeze-thaw cycles is too many, the gel network may become excessively dense, reducing the equilibrium swelling degree of the particles, the amount of sodium silicate solution adsorbed, and the subsequent release rate, making it difficult to balance particle integrity, liquid storage capacity, and controlled release performance, thus affecting the curing effect.
[0029] Optionally, the first drying method includes drying at 40~50 °C to constant weight.
[0030] Optionally, crushing and sieving can be used to obtain dry polymer particles with a particle size of 0.3 to 2.0 mm.
[0031] Optionally, the wetting method includes: spraying a nano-silica dispersion onto the surface of polymer particles in a tumbling state, maintaining the tumbling state so that the dispersion uniformly wets the particle surface and partially enters the shallow pores of the surface; as the ethanol-water mixed solvent gradually evaporates and is absorbed by the dried particles, the nano-silica contained therein gradually deposits and adsorbs on the particle surface; after there is no free liquid on the surface of the polymer particles, the nano-silica dispersion is sprayed again, repeating the spraying 6 to 10 times; multiple small-volume sprays prevent the particles from sticking together; the uniformity of the nano-silica distribution on the surface is improved by gradual deposition, and the problem of the dispersion penetrating into the deep layers of the polymer particles caused by soaking is avoided; the solid-liquid ratio of the polymer particles to all the nano-silica dispersion consumed is 1:0.8 to 0.85.
[0032] Optionally, the immersion is carried out in a drum with the drum speed maintained at 5~15 rpm, and the second drying method includes drying at 40~50 °C to constant weight.
[0033] Optionally, the dispersant in the nano-silica dispersion is an ethanol aqueous solution with a volume concentration of 75-85 vol%, the mass concentration of nano-silica in the nano-silica dispersion is 5-8 wt%, and the particle size of nano-silica is 10-50 nm, which can adhere to and embed into the surface layer of the second polymer particles. Compared with pure water, the selected ethanol aqueous solution can prevent the particles from absorbing too much water. Compared with anhydrous ethanol, it is more conducive to the adhesion of nano-silica. Compared with other types of dispersants, it can avoid problems such as surface silanol shielding, foam formation, and changes in cement hydration behavior caused by surfactant, polycarboxylate, or phosphate dispersant residues. If the particle size of nano-silica is too small, it is easy to agglomerate and cause uneven loading. If the particle size is too large, the specific surface area per unit mass and the surface reaction sites are reduced, which is not conducive to improving the particle-cement matrix interface performance.
[0034] Optionally, the concentration of the sodium silicate aqueous solution is 2-5 wt%, the liquid absorption time is 10-60 min, and the liquid absorption amount is 30-50% of the free liquid absorption ratio of the second polymer particles. If the liquid absorption amount is too low, there will be insufficient internal water storage and silicon source, making it difficult to play an effective role in the concrete curing process. If the liquid absorption amount is too high, the particles are prone to excessive expansion and softening, and are more likely to break or release liquid prematurely during stirring. A liquid absorption amount of 30-50% can achieve a balance between liquid storage, particle integrity, and remaining liquid absorption space. After that, the liquid is drained for 2-5 min to make the surface free of free liquid. The particle size of the second polymer in the dry state before liquid absorption is 0.3-2.0 mm, and the mass of the gel particles after liquid absorption is 2.2-4.0 times that of the second polymer particles. The free liquid absorption ratio refers to the liquid absorption mass of a unit dry particle calculated based on the mass difference before and after liquid absorption, after immersing the nano-silica loaded dry gel particles in a sodium silicate aqueous solution of the same concentration as the pre-absorption liquid at 20±1 ℃, absorbing the liquid until the mass no longer changes significantly, and draining the liquid for 3 min.
[0035] One or more embodiments of the present invention provide a high-strength porous concrete, comprising the following components in parts by weight: 570-670 parts cement, 90-150 parts fly ash, 90-120 parts silica fume, 550-650 parts quartz sand, 620-680 parts diabase fine aggregate, 155-195 parts water, 12-18 parts polycarboxylate superplasticizer, and 3.0-4.5 parts of the above-mentioned gel particles.
[0036] Of the above components, cement, fly ash, and silica fume are used to form cement-based materials, quartz sand is used as finer aggregate and filler, diabase fine aggregate is used to construct a larger-sized load-bearing skeleton, and the aforementioned gel particles are used to form cavities in high-strength porous concrete.
[0037] Optionally, the cement is 52.5 grade or 52.5R grade silicate cement or ordinary silicate cement, and the fly ash is grade I or grade II fly ash; the silica fume contains more than 95 wt% amorphous silica, has a specific surface area greater than 21.0 m² / g, a specific density greater than 2.2, and is an ultrafine dry powder that has not been fully densified.
[0038] Optionally, the quartz sand has a particle size of 0.16~2.36 mm, and the diabase fine aggregate is igneous rock fine aggregate obtained by crushing and screening diabase, with a particle size of 0.16~4.75 mm; the finer-grained quartz sand is used to fill the voids between the diabase fine aggregate, and the diabase fine aggregate is used to form a load-bearing skeleton. The two are combined to improve the particle packing density and reduce the original defects in the high-strength matrix.
[0039] Optionally, the water reduction rate of the polycarboxylate superplasticizer is not less than 25%.
[0040] One or more embodiments of the present invention provide a method for preparing the above-mentioned high-strength porous concrete, comprising the following steps: Cement, fly ash, and silica fume are mixed to obtain the first mixture; The first mixture, quartz sand, diabase fine aggregate, and 65-75% water by volume are mixed to obtain the second mixture; The second mixture, the gel particles, the remaining water, and the polycarboxylate superplasticizer are mixed to obtain a high-strength porous concrete mixture. The high-strength porous concrete mixture is poured, cured, demolded, and post-cured to obtain the high-strength porous concrete.
[0041] During the curing process, the surface nano-silica preferentially acts on the particle-cement matrix interface, and the reaction sites on the particle surface react with the Ca in the matrix. 2+ After the hydration reaction proceeds to form the hydration product CSH, the excess Ca in the solution... 2+ It can penetrate the polysaccharide film on the surface of the gel particles and enter the gel particles, promoting the release of water from the gel particles. At the same time, the silicon source stored inside the particles is released, and the sodium silicate pre-absorbed inside the particles is released during the water release process, providing a soluble silicon source for subsequent hydration reactions near the pore walls, forming a reinforced cavity wall structure inside the cement-based material. The two effects work together to improve the interface structure of the concrete cavity wall and enhance the stability of the pore structure. The reinforced cavity structure can reduce the apparent density and thermal conductivity of the material while maintaining compressive strength, and endow it with heat insulation, sound absorption and noise reduction functions.
[0042] In the above preparation process, the first mixture is obtained by low-speed stirring at a speed of 75-85 rpm for 2-3 minutes to prevent powder splashing; the second mixture is obtained by low-speed stirring at a speed of 75-85 rpm for 3-5 minutes to achieve thorough solid-liquid mixing; the high-strength porous concrete mixture is obtained by low-speed stirring at a speed of 75-85 rpm for 2-3 minutes until all solid raw materials are evenly dispersed and there is no obvious agglomeration; the gel particles are added after the cement-based mixture has completed the main stirring, and then low-speed stirring continues for 30-180 seconds to reduce gel particle breakage and the shedding of the surface nano-silica modified layer, and to ensure that the gel particles are evenly dispersed in the cement matrix.
[0043] Optionally, the specimen can be formed by light vibration or tamping during the casting process, and the surface of the specimen can be covered and cured after casting. It can be demolded after 24 hours.
[0044] Optionally, the conditions for maintenance and post-maintenance are standard maintenance conditions, including: temperature 20±2℃ and relative humidity >95%RH.
[0045] One or more embodiments of the present invention provide the application of the above-mentioned high-strength porous concrete in building energy-saving materials, building acoustic materials or traffic noise reduction materials.
[0046] Specifically, this includes applications in lightweight thermal insulation enclosure panels for field facilities and underground engineering, sound-absorbing hanging panels for elevated bridge railings, road sound barrier panels, prefabricated traffic noise reduction components, bridge auxiliary noise reduction panels, building partition wall blocks, prefabricated partition wall panels, or building enclosure panels.
[0047] To enable those skilled in the art to better understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below with reference to specific embodiments.
[0048] Example 1 A type of gel particle, prepared by the following method: Figure 1 As shown, it includes the following steps: Chia seed peel polysaccharide and polyvinyl alcohol were mixed at a dry weight ratio of 70:30 and stirred at low speed for 1.5 h to obtain an aqueous dispersion with a total solid content of 8 wt%. The aqueous dispersion was frozen at -20 ℃ for 10 h, thawed at 25 ℃ for 6 h, and then the freeze-thaw cycle was repeated twice (for a total of 3 freeze-thaw cycles). The mixture was then dried at 45 ℃ to constant weight, followed by crushing and sieving using a combination of 2 mm and 0.3 mm sieves to obtain polymer particles with a particle size of 0.3~2.0 mm.
[0049] A dispersant was prepared using ethanol and deionized water in a volume ratio of 8:2. Nano-silica with an average particle size of 30 nm was added to the dispersant, and the mixture was stirred at low speed for 13 min, followed by ultrasonic treatment for 20 min to obtain a 6 wt% nano-silica dispersion. Polymer particles were placed in a drum with an inner diameter of 15 cm and a rotation speed of 10 rpm. The nano-silica dispersion was sprayed onto the surface of the polymer particles until the dispersion uniformly wetted the particle surface and there was no free liquid. Spraying continued until all the nano-silica dispersion was sprayed in 8 stages, with a mass ratio of nano-silica dispersion to polymer particles of 0.833:1. The particles were then removed and dried at 40 °C to constant weight to obtain second polymer particles. The particle size (i.e., dry particle size) of the second polymer particles ranged from 0.3 to 2.0 mm, with an average of 1.1 mm.
[0050] Prepare a 3wt% sodium silicate solution, immerse the second polymer particles in the sodium silicate solution for 30 minutes for pre-absorption treatment; control the pre-absorption ratio to be 40% of the free absorption ratio of the second polymer particles, drain for 3 minutes to obtain gel particles.
[0051] The obtained gel particles consist of a hydrogel core and a nano-silica layer coating the hydrogel core. The raw materials for preparing the hydrogel core include chia seed peel polysaccharide and polyvinyl alcohol in a dry mass ratio of 7:3. Sodium silicate aqueous solution is adsorbed in the hydrogel core. The particle size distribution of the gel particles is 0.4 to 3.2 mm, with an average particle size of 1.8 mm, and the thickness of the nano-silica layer coating the surface is about 0.5 μm.
[0052] Example 1-1 A gel particle, the preparation method includes the following steps: Chia seed peel polysaccharide and polyvinyl alcohol were mixed at a dry weight ratio of 60:40 and stirred at low speed for 1.5 h to obtain an aqueous dispersion with a total solid content of 7 wt%. The aqueous dispersion was frozen at -20 ℃ for 8 h, thawed at 20 ℃ for 4 h, and the freeze-thaw cycle was repeated twice, for a total of 3 freeze-thaw cycles. Subsequently, it was dried at 40 ℃ to constant weight, crushed, and sieved using a combination of 2 mm and 0.3 mm sieves to obtain polymer particles with an average particle size of 1.1 mm.
[0053] A 75 vol% ethanol dispersant was prepared using ethanol and deionized water. Nano-silica with an average particle size of 10 nm was added to the dispersant. After low-speed stirring for 13 min and ultrasonic treatment for 20 min, a dispersion with a nano-silica concentration of 5 wt% was obtained. Polymer particles were placed in a 15 cm inner diameter drum rotating at 10 rpm, and the nano-silica dispersion was sprayed in stages while the particles were continuously tumbling. After each spray, the dispersion was allowed to uniformly wet the particle surface until no free liquid remained before the next spray was performed. The entire dispersion was sprayed in 6 stages. The mass ratio of nano-silica dispersion to polymer particles consumed was 0.80:1. The particles were removed and dried at 40 °C to constant weight to obtain second polymer particles. The average particle size (i.e., dry particle size) of the second polymer particles was 1.1 mm.
[0054] Prepare a 2 wt% sodium silicate aqueous solution, immerse the second polymer particles in it for 10 min for pre-absorption treatment; control the pre-absorption ratio to be 30% of the free absorption ratio of the second polymer particles in the same concentration of sodium silicate aqueous solution, and then drain for 2 min to obtain gel particles.
[0055] The requirements for each raw material and other preparation methods are the same as in Example 1.
[0056] Examples 1-2 Chia seed peel polysaccharide and polyvinyl alcohol were mixed at a dry weight ratio of 80:20 and stirred at low speed for 1.5 h to obtain an aqueous dispersion with a total solid content of 10 wt%. The aqueous dispersion was frozen at -10 ℃ for 12 h, thawed at 30 ℃ for 8 h, and then the freeze-thaw cycle was repeated twice, for a total of 3 freeze-thaw cycles. Subsequently, it was dried at 50 ℃ to constant weight, crushed, and sieved using a combination of 2 mm and 0.3 mm sieves to obtain polymer particles with an average particle size of 1.1 mm.
[0057] A dispersant with an ethanol volume fraction of 85 vol% was prepared using ethanol and deionized water. Nano-silica with an average particle size of 50 nm was added to the dispersant. After low-speed stirring for 13 min and ultrasonic treatment for 20 min, a dispersion with a nano-silica mass concentration of 8 wt% was obtained. Polymer particles were placed in a drum with an inner diameter of 15 cm and a rotation speed of 10 rpm. The nano-silica dispersion was sprayed in stages while the particles were continuously tumbling. After each spray, the dispersion was allowed to uniformly wet the particle surface until no free liquid remained on the surface before the next spray was performed. The entire dispersion was sprayed in 10 stages. The mass ratio of nano-silica dispersion to polymer particles consumed was 0.85:1. The particles were removed and dried at 50 °C to constant weight to obtain second polymer particles. The average particle size (i.e., dry particle size) of the second polymer particles was 1.1 mm.
[0058] Prepare a 5 wt% sodium silicate aqueous solution, immerse the second polymer particles in it for 60 min for pre-absorption treatment; control the pre-absorption ratio to be 50% of the free absorption ratio of the second polymer particles in the same concentration of sodium silicate aqueous solution, and then drain for 5 min to obtain gel particles.
[0059] The requirements for each raw material and other preparation methods are the same as in Example 1.
[0060] Comparative Example 1 A type of gel particle differs from Example 1 in that: instead of using a second polymer particle for soaking, the polymer particle is directly soaked in a sodium silicate solution. The other preparation methods are the same as in Example 1. The gel particle obtained differs from that in Example 1 in that: there is no nano-silica layer on the surface.
[0061] Comparative Example 2 A type of gel particle differs from Example 1 in that: the second polymer particle is placed in deionized water for pre-absorption treatment, and the pre-absorption ratio is controlled to be 40% of the free absorption ratio of the second polymer particle; the obtained gel particle differs from Example 1 in that: water is adsorbed in the hydrogel core material instead of sodium silicate aqueous solution.
[0062] Comparative Example 3 The preparation method of a gel particle differs from that of Example 1 in that: chia seed peel polysaccharide is not used, and only polyvinyl alcohol is used as a raw material to prepare an aqueous dispersion; the other preparation methods are the same as those in Example 1.
[0063] Comparative Example 4 A gel particle, the preparation method of which differs from that of Example 1 is: chia seed peel polysaccharide is replaced with the same mass of corn root mucilage polysaccharide, while other raw materials and preparation methods are the same as in Example 1.
[0064] Example 2 Existing hydrogel-based internal curing materials may suffer damage, premature water loss, or leakage during concrete mixing and early hydration, affecting their stable pore formation and sustained internal curing effect. Furthermore, the pore interfaces formed after hydrogel shrinkage are typically weak, easily leading to a decrease in pore wall strength and potentially adversely affecting the flowability, mechanical properties, and durability of concrete. Some existing modified hydrogels primarily focus on water absorption, storage, and release, lacking functional structures that can participate in hydration reactions at different stages. The pores and interface regions formed after water release are difficult to continuously strengthen, and the chemical reagents used in hydrogel modification often affect the hydrogel's structure, preventing the full release of its properties.
[0065] The introduction of cavities reduces the effective load-bearing area within concrete and creates stress concentration around the cavities. To mitigate the adverse effects of cavity structures on mechanical properties, high-strength porous concrete typically employs a lower water-cement ratio to enhance the density and load-bearing capacity of the cement matrix. However, under low water-cement ratio conditions, there is less free water available for hydration reactions within the concrete. During continuous cement hydration, this leads to a decrease in internal relative humidity, self-drying, and self-shrinkage, increasing the risk of early cracking. Therefore, how to form a stable cavity structure while avoiding the degradation of modified hydrogel properties by chemical reagents, and how to introduce multi-energy internal curing materials with controllable water storage, controlled water release, and pore wall interface reinforcement to improve the internal humidity environment of concrete and reduce the adverse effects of cavities on mechanical properties, is a crucial technical problem that urgently needs to be solved in the preparation of high-strength porous concrete.
[0066] This embodiment provides a high-strength porous concrete, comprising the following components in parts by weight: 618 parts cement, 122 parts fly ash, 108 parts silica fume, 176 parts water, 603 parts quartz sand, 647 parts diabase fine aggregate, 15.2 parts polycarboxylate superplasticizer and 3.8 parts gel particles prepared in Example 1.
[0067] The cement is 52.5 grade silicate cement; the fly ash is grade I fly ash; the silica fume contains approximately 95 wt% amorphous silica, has a specific surface area of approximately 21.0 m² / g, a specific density greater than 2.2, and is an ultrafine dry powder that has not been fully densified.
[0068] The quartz sand has a particle size range of 0.16~2.36 mm, which meets the relevant requirements for Class I sand in GB / T 14684—2022 "Sand for Construction"; the fine aggregate of diabase has a particle size range of 0.16~4.75 mm, which meets the relevant requirements for Class I manufactured sand in GB / T 14684—2022 "Sand for Construction".
[0069] Preparation methods include: Cement, fly ash, and silica fume are mixed and stirred at low speed for 3 minutes to obtain the first mixture. Quartz sand, diabase fine aggregate, and 123 parts water are added to the first mixture and stirred at low speed for 5 minutes to obtain the second mixture. The remaining water and polycarboxylate superplasticizer are added to the second mixture and stirred at low speed for 3 minutes. Then gel particles are added and stirred at low speed for 60 seconds to obtain a high-strength porous concrete mixture.
[0070] The high-strength porous concrete mixture was poured into shape, covered and cured for 24 hours, then demolded, and cured for 28 days at 20±2 ℃ and relative humidity not less than 95% to obtain high-strength porous concrete.
[0071] The gel particles swell after pre-absorbing the liquid and gradually release the liquid and shrink during cement hydration. The cavity size is not strictly identical to the gel particle size. The cavity size is distributed between 0.9 and 4.5 mm, and the cavity volume accounts for 0.4%.
[0072] By utilizing the properties of modified chia seed mucilage particles to expand upon liquid absorption and shrink upon water release, a relatively uniform pore structure is formed within the cement matrix; such as Figure 3 As shown in (A), in the initial stage, the nano-silica on the particle surface can react with the calcium components near the pore walls, promoting the formation of calcium silicate hydration products and filling the pore wall interface region, thereby strengthening the pore walls, improving weak interfaces, and enhancing the stability of the pore structure. Furthermore, the abundant natural hydrophilic groups on the surface of the chia seed mucilage particles can fully combine with polyvinyl alcohol and nano-silica, avoiding the need for excessive chemical reagents to fix the nano-silica. Figure 3 As shown in (B), during the outer reaction stage, as cement hydration proceeds, the nano-silica on the particle surface gradually reacts with Ca(OH)2 near the pore walls to form CSH-type hydration products. Figure 3 As shown in (C), during the water release and silicon release stage, excess Ca... 2+ Entering the three-dimensional network structure, with the Ca²⁺ in the pore solution +Increased concentration and ionic strength lead to decreased electrostatic repulsion between polysaccharide chains and reduced network osmotic pressure. This causes the gel network to shrink and release some stored water and silicon source. Hydration reactions continue near the pore walls, generating CSH-type hydration products. This ensures good liquid storage stability during concrete mixing and early hydration stages, reducing premature water loss, liquid leakage, and particle breakage, thus controlling water release. This, in turn, affects the properties of the modified chia seed mucilage particles themselves. The gel particles act as a storage and slow-release carrier for the silicon-containing reaction solution, pre-adsorbing a low concentration of sodium silicate solution. During water release, the modified chia seed mucilage particles simultaneously release water and active silicon source. The released water promotes continuous hydration of the cementitious material near the pore walls, and the active silicon source further reacts with the calcium components. Figure 3 As shown in (D), during the pore wall reinforcement stage, the gel particles form functional cavities after completing the main liquid release and shrinkage. The CSH-enriched pore wall region, jointly promoted by the surface nano-silica and the internal released silicon source, forms an interface reinforcement region around the pores where calcium silicate hydration products are enriched. The synergistic effect of the internal and external silicon sources enables the material to form a porous structure while taking into account internal curing, pore wall reinforcement and the maintenance of mechanical properties.
[0073] The characterization results of the void structure under electron microscopy are as follows: Figure 2 As shown, the inner surface of the pore wall inside the cavity is relatively smooth, forming a continuously distributed layer of hydration products. The area on the outer side of the pore wall connected to the cement matrix is relatively rough, with hydration products interlocking with the surrounding cement matrix to form a continuous transition zone on the outer side of the pore wall. The enrichment of hydration products on the inner surface of the pore wall is mainly related to the nano-silica loaded on the surface of the gel particles. The nano-silica reacts with the calcium components in the pore solution, promoting the generation of hydration products, mainly CSH-type products, near the original particle-matrix interface, thereby filling the pore wall defects and improving the density of the pore wall. The outer side of the pore wall is affected by the combined effect of the internal curing of water released by the gel particles and the active silicon source provided by the internal sodium silicate, promoting the continued hydration of adjacent cementitious materials, allowing the hydration products to gradually transition from the pore wall to the cement matrix, eventually forming a surface hydration product layer. The synergistic effect of the inner and outer structures can improve the interfacial continuity between the pore wall and the cement matrix, reduce the porosity and stress concentration at the pore edge, improve the stability and local load-bearing capacity of the pore wall, thereby reducing the adverse effect of the cavity on the compressive strength of concrete.
[0074] Example 3 A high-strength porous concrete comprises the following components in parts by weight: 570 parts cement, 90 parts fly ash, 90 parts silica fume, 155 parts water, 550 parts quartz sand, 620 parts diabase fine aggregate, 12 parts polycarboxylate superplasticizer, and 3.0 parts gel particles prepared in Example 1.
[0075] The requirements for each raw material and the preparation method are the same as in Example 2.
[0076] Example 4 A high-strength porous concrete comprises the following components in parts by weight: 670 parts cement, 150 parts fly ash, 120 parts silica fume, 195 parts water, 650 parts quartz sand, 680 parts diabase fine aggregate, 18 parts polycarboxylate superplasticizer, and 4.5 parts gel particles prepared in Example 1.
[0077] The requirements for each raw material and the preparation method are the same as in Example 2.
[0078] Comparative Example 5 A high-strength porous concrete comprises the following components in parts by weight: The mixture consisted of 618 parts cement, 122 parts fly ash, 108 parts silica fume, 176 parts water, 603 parts quartz sand, 647 parts diabase fine aggregate, and 15.2 parts polycarboxylate superplasticizer. The difference from Example 2 was that gel particles were not added.
[0079] The other raw materials and preparation methods are the same as in Example 2.
[0080] Comparative Example 6 A high-strength porous concrete comprises the following components in parts by weight: The mixture consisted of 618 parts cement, 122 parts fly ash, 108 parts silica fume, 176 parts water, 603 parts quartz sand, 647 parts diabase fine aggregate, 15.2 parts polycarboxylate superplasticizer, and 3.8 parts gel particles prepared in Comparative Example 1. The difference from Example 2 was that the gel particles of Example 1 were replaced with those of Comparative Example 1.
[0081] The other raw materials and preparation methods are the same as in Example 2.
[0082] Comparative Example 7 A high-strength porous concrete comprises the following components in parts by weight: The mixture consisted of 618 parts cement, 122 parts fly ash, 108 parts silica fume, 176 parts water, 603 parts quartz sand, 647 parts diabase fine aggregate, 15.2 parts polycarboxylate superplasticizer, 3.8 parts gel particles prepared in Comparative Example 1, and 0.19 parts nano-silica. The difference from Example 2 was that the gel particles of Example 1 were replaced with those of Comparative Example 1, and an equal amount of nano-silica was added as a separate component, similar to that in Example 2.
[0083] Accordingly, in the preparation method, after preparing the nano-silica dispersion according to the method of Example 1, the nano-silica dispersion is added to the second mixture during the preparation of high-strength porous concrete.
[0084] The other raw materials and preparation methods are the same as in Example 2.
[0085] Comparative Example 8 A high-strength porous concrete comprises the following components in parts by weight: The mixture consisted of 618 parts cement, 122 parts fly ash, 108 parts silica fume, 176 parts water, 603 parts quartz sand, 647 parts diabase fine aggregate, 15.2 parts polycarboxylate superplasticizer, and 3.8 parts gel particles prepared in Comparative Example 2. The difference from Example 2 was that the gel particles from Example 1 were replaced with those from Comparative Example 2. The amount of internal curing water provided by the gel particles was the same as in Example 2.
[0086] The other raw materials and preparation methods are the same as in Example 2.
[0087] Comparative Example 9 A high-strength porous concrete comprises the following components in parts by weight: The mixture consisted of 618 parts cement, 122 parts fly ash, 108 parts silica fume, 176 parts water, 603 parts quartz sand, 647 parts diabase fine aggregate, 15.2 parts polycarboxylate superplasticizer, and 3.8 parts gel particles prepared in Comparative Example 3. The difference from Example 2 was that the gel particles from Example 1 were replaced with the gel particles from Comparative Example 3.
[0088] The other raw materials and preparation methods are the same as in Example 2.
[0089] Comparative Example 10 A high-strength porous concrete comprises the following components in parts by weight: The mixture consisted of 618 parts cement, 122 parts fly ash, 108 parts silica fume, 176 parts water, 603 parts quartz sand, 647 parts diabase fine aggregate, 15.2 parts polycarboxylate superplasticizer, and 3.8 parts gel particles prepared in Comparative Example 4. The difference from Example 2 was that the gel particles from Example 1 were replaced with the gel particles from Comparative Example 4.
[0090] The other raw materials and preparation methods are the same as in Example 2.
[0091] Test case High-strength porous concrete provided in each example and comparative example was taken after 28 days of curing and placed in an environment with a temperature of 20±2℃ and a relative humidity of 50±5% for 24 hours to equilibrate the specimens in each group to ensure that the specimens are in the same moisture content. I. Conduct autogenous shrinkage rate testing; according to ASTM C1698-19 "Test Method for Autogenous Strain of Cement Paste and Mortar", the method includes: using the sealed corrugated tube method, filling freshly mixed concrete into a low-density polyethylene corrugated tube with a length of 420±5 mm and an outer diameter of 29±0.5 mm. During filling, the tube wall is gently vibrated or tapped in sections to remove obvious air bubbles. After filling, sealing plugs are installed at both ends to prevent moisture exchange between the specimen and the outside environment. The specimen is placed in a constant temperature environment of 20±1℃, and the length change is recorded at 1 day, 3 days, 7 days, 14 days, and 28 days, with the final setting time as the starting point of the autogenous shrinkage test. The autogenous shrinkage rate is calculated according to the following formula: ; In the formula: ε t The autocontraction at age t is expressed in με. L0 is the reference length of the specimen at final setting; L t The specimen length is t at the specified age.
[0092] II. Average sound absorption coefficient testing was conducted according to GB / T 18696.2-2002 "Measurement of Sound Absorption Coefficient and Acoustic Impedance in Acoustic Impedance Tubes - Part 2: Transfer Function Method". The method included the use of a dual-microphone impedance tube method. The testing device included an impedance tube, a sound source, a power amplifier, two microphones, a specimen clamping end, a data acquisition system, and a frequency analysis system. Cylindrical specimens were prepared according to the inner diameter of the impedance tube, with a uniform thickness of 30 mm. The specimen diameter matched the inner diameter of the impedance tube. To cover the 100~4000 Hz range, large-diameter and small-diameter impedance tubes suitable for low and high frequency bands were used respectively. During testing, the specimen was installed at the end of the impedance tube, with a rigid backplate on the back. The outer periphery of the specimen was tightly fitted to the tube wall, and a thin layer of sealing material was used to seal the edge gaps to prevent sound leakage. The sound source emitted broadband random noise or a swept-frequency signal within a specified frequency range. The sound pressure transfer function was measured using the two microphones, and the normal incident sound absorption coefficient at different frequencies was calculated.
[0093] The sound absorption coefficient is calculated using the following formula: ; In the formula: For frequency Normal incident sound absorption coefficient; denoted as the complex reflection coefficient of the specimen surface.
[0094] The sound absorption coefficients were recorded at 17 1 / 3 octave band center frequencies: 100 Hz, 125 Hz, 160 Hz, 200 Hz, 250 Hz, 315 Hz, 400 Hz, 500 Hz, 630 Hz, 800 Hz, 1000 Hz, 1250 Hz, 1600 Hz, 2000 Hz, 2500 Hz, 3150 Hz, and 4000 Hz.
[0095] The average sound absorption coefficient within the specified frequency range is calculated using the following formula: ; In the formula: The average sound absorption coefficient; For the first The sound absorption coefficient at each center frequency; The number of frequency points participating in the averaging calculation is specified in this test case. .
[0096] The average sound absorption coefficient in the results is the average of the sound absorption coefficients at each frequency point within the specified frequency range. The larger the coefficient, the stronger the ability of the specimen to absorb incident sound energy.
[0097] III. The thermal conductivity was tested using the steady-state protective hot plate method. According to GB / T 10294-2008 "Determination of Steady-State Thermal Resistance and Related Properties of Insulation Materials - Protective Hot Plate Method", the testing apparatus included a metering hot plate, a protective hot plate, a constant-temperature cold plate, a specimen clamping assembly, a temperature sensor, a heat flux measurement device, and a data acquisition system. The thermally conductive specimen was prepared as a plate-shaped specimen with dimensions of 300mm × 300mm × 30mm. Before testing, the actual thickness of the specimen was measured, and both sides of the specimen were ensured to be flat and parallel. During testing, the specimen was clamped between the constant-temperature hot plate and the constant-temperature cold plate, ensuring full contact between the specimen surface and the hot and cold plates, avoiding significant air gaps. The temperature of the constant-temperature hot plate was set to 35±0.5℃, and the temperature of the constant-temperature cold plate was set to 15±0.5℃, allowing heat to be stably transferred along the thickness direction of the specimen. After the temperatures on both sides of the specimen and the heat flux density through the specimen reached a stable state, the surface temperatures on both sides of the specimen, the actual thickness of the specimen, and the stable heat flux density were recorded.
[0098] Thermal conductivity is calculated using the following formula: ; In the formula: is the thermal conductivity, with units of W / (m·K); The steady-state heat flux density of the specimen is expressed in W / m². The actual thickness of the specimen is expressed in meters (m). The temperature difference between the two surfaces of the specimen is expressed in K.
[0099] Thermal conductivity indicates a material's ability to transfer heat. The lower the value, the weaker the material's heat transfer capacity and the better its thermal insulation performance.
[0100] The test results are shown in Table 1.
[0101] Table 1. Performance test results of high-strength porous concrete in each comparative example and embodiment.
[0102] The corresponding statistical charts of compressive strength and shrinkage rate are as follows: Figure 4 As shown in the figure, the statistical graphs of average sound absorption coefficient and thermal conductivity are as follows: Figure 5 As shown.
[0103] It can be seen that the compressive strength of Example 2 is 90 MPa, the self-shrinkage rate is 293 με, the average sound absorption coefficient is 0.15, and the thermal conductivity is 1.63 W / (m·K). Compared with Comparative Example 5, the average sound absorption coefficient of Example 2 is increased by about 66.7%, the thermal conductivity is decreased by about 20.1%, and the self-shrinkage rate is decreased by about 67.7%. This result indicates that after introducing modified chia seed mucilage particles, the sound absorption performance, heat insulation performance, and water retention capacity of the material are significantly improved. The compressive strength of Example 2 is slightly lower than that of Comparative Example 5, but it still remains at or above 90 MPa, indicating that the material maintains high mechanical properties while maintaining a low self-shrinkage rate, good sound absorption performance, and certain heat insulation performance.
[0104] Compared to Comparative Example 6, Example 2 showed an increase in compressive strength of approximately 26.8%, an increase in average sound absorption coefficient of approximately 25.0%, a decrease in self-shrinkage rate of approximately 32.2%, and an increase in thermal conductivity of approximately 5.8%. The chia seed sap particles in Comparative Example 6 did not have attached nano-silica. These results indicate that unmodified chia seed sap particles can alter the internal structure of the cement matrix to some extent, improving its sound absorption and curing properties. However, due to the lack of nano-silica at the pore interfaces to provide reaction sites, relatively few CSH-type hydration products are generated near the pore walls. The pore walls and interfaces are relatively loose, resulting in poor continuity of the internal solid heat transfer path, leading to weaker pore wall strength and a slightly lower thermal conductivity compared to Example 1. This means the material cannot simultaneously possess sound absorption, thermal insulation, curing, and mechanical properties.
[0105] Compared to Comparative Example 7, Example 2 showed an increase in compressive strength of approximately 9.8%, an increase in average sound absorption coefficient of approximately 36.4%, a decrease in autogenous shrinkage of approximately 35.7%, and a decrease in thermal conductivity of approximately 3.0%. Comparative Example 7 involved directly adding the same amount of nano-silica as Example 2 to the concrete matrix. This result indicates that nano-silica has difficulty concentrating its effect on the pore wall region formed after the shrinkage of chia seed mucilage particles, resulting in weaker pore wall strength. This result demonstrates that, compared to directly incorporating an equal amount of nano-silica into the cement matrix, attaching it to the surface of chia seed mucilage particles can improve the efficiency of nano-silica in the pore wall region, which is beneficial for simultaneously improving compressive strength, autogenous shrinkage control, sound absorption performance, and thermal insulation performance.
[0106] Compared to Comparative Example 8, Example 2 showed an increase in compressive strength of approximately 13.9%, an increase in average sound absorption coefficient of approximately 7.1%, a decrease in self-shrinkage rate of approximately 13.1%, and an increase in thermal conductivity of approximately 3.8%. Comparative Example 8 used an equal amount of deionized water to replace the sodium silicate pre-absorption solution. These results indicate that the chia seed mucilage particles lack an internal active silicon source, resulting in relatively fewer CSH-type hydration products, a relatively loose overall structure, a relatively low thermal conductivity, and relatively weak pore wall strength. This suggests that the internal sodium silicate and the surface nano-silica have a synergistic reinforcing effect.
[0107] Compared to Comparative Example 9, Example 2 showed an approximately 9.8% increase in 28-day compressive strength, an approximately 25.0% increase in average sound absorption coefficient, an approximately 25.8% decrease in 28-day self-shrinkage rate, and an approximately 5.8% decrease in thermal conductivity. Comparative Example 9 used only polyvinyl alcohol to prepare the hydrogel core material. While its gel particles had a high gel fraction and particle integrity, its free liquid absorption ratio was low, and it lacked the branched polysaccharide chains, carboxyl sites, and ion-responsive structures provided by chia seed peel polysaccharide. This resulted in a higher premature leakage rate of sodium silicate in the simulated pore solution, and Ca²⁺… + The shrinkage and release response under the action was weak. This result indicates that the composite network formed by chia seed peel polysaccharide and polyvinyl alcohol does not simply improve particle strength, but rather helps to simultaneously improve liquid storage capacity, reduce premature leakage, and regulate the release of water and silicon sources, thereby improving the autogenous shrinkage control, pore structure, and pore wall stability of concrete.
[0108] Compared to Comparative Example 10, Example 2 showed an approximately 16.9% increase in 28-day compressive strength, an approximately 36.4% increase in average sound absorption coefficient, a approximately 31.9% decrease in 28-day self-shrinkage rate, and an approximately 8.4% decrease in thermal conductivity. Comparative Example 10 used corn root mucilage polysaccharide to replace chia seed coat polysaccharide by an equal amount. Although corn root mucilage polysaccharide also contains hydroxyl and uronic acid groups, its supramolecular network is relatively loose, resulting in lower wettability and water-binding capacity. This led to lower gel fraction, lower nano-silica loading, and lower particle integrity after stirring in the composite gel particles formed with polyvinyl alcohol. Simultaneously, it exhibited a higher premature sodium silicate leakage rate in the simulated pore solution. These results indicate that mucilage polysaccharides from different plant sources cannot be simply substituted for each other; the composite network formed by chia seed coat polysaccharide and polyvinyl alcohol is more conducive to balancing particle stability, sodium silicate storage, and Ca²⁺. + The response to liquid release and pore wall enhancement results in better mechanical properties, self-shrinkage control, sound absorption and heat insulation effects.
[0109] In summary, Example 1 utilizes the freeze-thaw crosslinking of chia seed coat mucilage and polyvinyl alcohol to form a stable chia seed mucilage particle core, with nano-silica adhering to the outer surface of the particles and pre-absorbing sodium silicate solution inside, thus constructing composite chia seed mucilage particles. When these particles are incorporated into concrete, they can store and gradually release moisture during hydration, improving the internal humidity environment of the low water-cement ratio matrix and reducing autogenous shrinkage. The pores formed after the particles release water and shrink can improve the sound absorption and thermal insulation properties of the material. The stable three-dimensional network structure of the modified chia seed mucilage particles and the abundance of CSH-type hydration products generated near the pore walls enhance the stability of the pore walls. The high-strength porous concrete made from modified chia seed mucilage particles of this invention, while forming stable functional pores, providing internal curing, and reducing autogenous shrinkage, can also reduce the adverse effects of pore formation on compressive strength through localized reinforcement of the pore walls, giving the material both high mechanical properties, good sound absorption properties, and good thermal insulation properties.
[0110] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A gel particle, characterized in that... The hydrogel core material includes a hydrogel core material and a nano-silica layer covering the hydrogel core material. The raw materials for preparing the hydrogel core material include chia seed peel polysaccharide and polyvinyl alcohol in a dry mass ratio of (6~8):(2~4). The hydrogel core material contains sodium silicate aqueous solution.
2. The gel particles as described in claim 1, characterized in that, The concentration of the sodium silicate aqueous solution is 2-5 wt%, and the sodium silicate aqueous solution accounts for 60-90 wt% of the hydrogel core material; the particle size of the gel particles is 0.4-3.2 mm, and the thickness of the nano-silica layer is 0.1-1.0 μm.
3. A method for preparing gel particles as described in any one of claims 1-2, characterized in that, Chia seed peel polysaccharide and polyvinyl alcohol were mixed in a set mass ratio to form a mixture, and then the mixture was freeze-thawed to obtain a hydrogel. After drying, crushing and sieving, polymer particles were obtained. The surface of polymer particles is wetted with a nano-silica dispersion and then dried to obtain a second polymer particle with an externally coated nano-silica layer. The second polymer particles were placed in an aqueous sodium silicate solution and absorbed to obtain the gel particles.
4. The method for preparing gel particles as described in claim 3, characterized in that, The freeze-thaw cycle method includes freezing the mixture at -20 to -10 °C for 8 to 12 hours, then thawing it at 20 to 30 °C for 4 to 8 hours, and repeating the freeze-thaw treatment 2 to 3 times.
5. The method for preparing gel particles as described in claim 3, characterized in that, The impregnation method includes: spraying a nano-silica dispersion onto the surface of polymer particles in a tumbling state, maintaining the tumbling state, and continuing to spray the nano-silica dispersion after there is no free liquid, repeating the spraying 6 to 10 times; the solid-liquid ratio of the polymer particles to all the nano-silica dispersion consumed is 1:0.8 to 0.
85.
6. The method for preparing gel particles as described in claim 5, characterized in that, The dispersant in the nano-silica dispersion is an aqueous ethanol solution with a volume concentration of 75-85 vol%, the mass concentration of nano-silica in the nano-silica dispersion is 5-8 wt%, and the particle size of nano-silica is 10-50 nm.
7. The method for preparing gel particles as described in claim 3, characterized in that, The concentration of the sodium silicate aqueous solution is 2-5 wt%, the absorption time is 10-60 min, and the absorption volume is 30-50% of the free absorption ratio of the second polymer particles.
8. A high-strength porous concrete, characterized in that, The components include the following parts by weight: 570-670 parts cement, 90-150 parts fly ash, 90-120 parts silica fume, 550-650 parts quartz sand, 620-680 parts diabase fine aggregate, 155-195 parts water, 12-18 parts polycarboxylate superplasticizer, and 3.0-4.5 parts gel particles as described in any one of claims 1-2.
9. A method for preparing high-strength porous concrete according to claim 8, characterized in that, Includes the following steps: Cement, fly ash, and silica fume are mixed to obtain the first mixture; The first mixture, quartz sand, diabase fine aggregate, and 65-75% water by volume are mixed to obtain the second mixture; The second mixture, gel particles, remaining water, and polycarboxylate superplasticizer are mixed to obtain a high-strength porous concrete mixture. The high-strength porous concrete mixture is poured, cured, demolded, and post-cured to obtain the high-strength porous concrete.
10. The application of the high-strength porous concrete as described in claim 8 in building energy-saving materials, building acoustic materials, or traffic noise reduction materials.